IDENTIFIKASI FRAGMENTASI LAHAN PADA PERI-URBAN KAWASAN PERKOTAAN CEKUNGAN BANDUNG (STUDI KASUS: KABUPATEN BANDUNG) - Nadhifa, Nisrina
Land fragmentation is a peri-urban phenomenon that shows the division of plots in a land use and makes it separate from the whole structure so that it is isolated from other activities. The identification of land fragmentation was carried out in Bandung Re gency as a peri-urban Metropolitan Bandung Area which experienced a devolution of activities from the core urban area and became an intensive urban rural transition zone with unpatterned development. Land fragmentation was measured by the Fragstats application based on indicators of total area, number of patch, patch size, patch size dispersion, patch shape, patch division, patch splitting, and effective mesh size in a land use. Land Fragmentation Index is generated by normalizing the indicator values using the mean standardization method and by weighting the indicators using the entropy weight method. Land fragmentation in Bandung Regency fluctuated for each land use in 2013, 2018, and 2020, with the highest land fragmentation index in residential areas. Some of the peri-urban characteristics of Bandung Regenc y such as road accessibility, distance to the district center and core city, high school education units, residential and agricultural land use, and population intensity can significantly affect the occurrence of land fragmentation so that these characteristics need to be considered for development. Land fragmentation can result in a shift in the spatial structure between the development areas of Bandung Regency. Land fragmentation can be avoided through a spatial planning mechanism that takes into account spatial patterns, land functions, and the direction of change in peri -urban areas.